ENHANCING BUSINESS PERFORMANCE OF SAHID MONTANA HOTEL MALANG IN TOURISM PROGRAM - Novia Larasati; Gusti Ayu Shinta; Dennis Mahendra; Vanessa Sanchez; Pinandita Denisa; Della Fany Yulza; Naser B M AA Almutari (AIBPM Publisher, 2018)
Sahid montana is a 5 star hotel located in Malang. The hotel has a herritage-themed design, which makes Sahid hotel has its own advantages from other hotels. Sahid Montana wants his hotel to be known internationally. The idea for Sahid Montana if want go international are to create an attractive package for the tourists so will be interested and create activities such as learning traditional dance and learning to make batik. Sahid Montana does not have a target country because Sahid Montana wants all customers from all the countries can stay at Sahid Hotel. If want to succeed until the international level it will require some strategies in doing promotions such as creating websites and join some events in Festival Beautiful Indonesia in abroad.